Chemical and biological properties of phosphorus-fertilized soil under legume and grass cover (Cerrado region, Brazil) - Souza, Marcelo Fernando Pereira [UNESP]; Silva, Mariana Pina Da [UNESP]; Arf, Orivaldo [UNESP]; Cassiolato, Ana Maria Rodrigues [UNESP] (Sociedade Brasileira de Ciência do Solo, 2013)
The use of cover crops has been suggested as an effective method to maintain and/or increase the organic matter content, while maintaining and/or enhancing the soil physical, chemical and biological properties. The fertility of Cerrado soils is low and, consequently, phosphorus levels as well. Phosphorus is required at every metabolic stage of the plant, as it plays a role in the processes of protein and energy synthesis and influences the photosynthetic process. This study evaluated the influence of cover crops and phosphorus rates on soil chemical and biological properties after two consecutive years of common bean. The study analyzed an Oxisol in Selvíria (Mato Grosso do Sul, Brazil), in a randomized block, split plot design, in a total of 24 treatments with three replications. The plot treatments consisted of cover crops (millet, pigeon pea, crotalaria, velvet bean, millet + pigeon pea, millet + crotalaria, and millet + velvet bean) and one plot was left fallow. The subplots were represented by phosphorus rates applied as monoammonium phosphate (0, 60 and 90 kg ha-1 P2O5). In August 2011, the soil chemical properties were evaluated (pH, organic matter, phosphorus, potential acidity, cation exchange capacity, and base saturation) as well as biological variables (carbon of released CO2, microbial carbon, metabolic quotient and microbial quotient). After two years of cover crops in rotation with common bean, the cover crop biomass had not altered the soil chemical properties and barely influenced the microbial activity. The biomass production of millet and crotalaria (monoculture or intercropped) was highest. The biological variables were sensitive and responded to increasing phosphorus rates with increases in microbial carbon and reduction of the metabolic quotient.

A utilização de plantas de cobertura é sugerida como método fundamental para manter e, ou, elevar o teor de matéria orgânica no solo, mantendo e, ou, melhorando as condições físicas, químicas e biológicas dele. Os solos do Cerrado apresentam baixa fertilidade, consequentemente baixos teores de fósforo (P), que se relacionam a todas as etapas metabólicas da planta, por essas fazerem parte dos processos de síntese proteica e energética, além de interferir no processo fotossintético. Este trabalho objetivou avaliar a influência de plantas de coberturas e doses de P sobre os atributos químicos e biológicos do solo. O trabalho foi conduzido em Selvíria, MS, em Latossolo Vermelho distrófico, com delineamento de blocos casualizados em esquema de parcelas subdivididas, com plantas de cobertura (milheto, guandu, crotalária, mucuna-preta, milheto + guandu, milheto + crotalária e milheto + mucuna-preta) e pousio nas parcelas e doses de P (0, 60 e 90 kg ha-1 de P2O5, na forma de monoamônio fosfato), nas subparcelas, totalizando 24 tratamentos, com três repetições. Em agosto de 2011, foram avaliados os atributos químicos (pH, matéria orgânica, fósforo, acidez potencial, capacidade de troca catiônica e saturação por bases) e biológicos do solo (carbono do CO2 liberado, carbono microbiano, quociente metabólico e quociente microbiano do solo). Após dois anos de cultivo das plantas de cobertura em rotação com o feijoeiro, verificou-se que a biomassa das plantas de cobertura não alterou as características químicas do solo e pouco influenciou sobre a atividade microbiana. As maiores respostas foram verificadas para milheto e crotalária, isoladas ou em consórcio. As variáveis biológicas foram sensíveis e responderam às doses crescentes de adubação fosfatada, sendo os aumentos do carbono microbiano e a redução do quociente metabólico obtidos com as maiores doses de P.
Atributos químicos e biológicos do solo com cobertura de leguminosas, gramínea e doses de fósforo, em região de Cerrado, Brasil
Keywords: carbono microbiano; atividade microbiana; matéria orgânica; adubação verde; cerrado; microbial biomass carbon; microbial activity; organic matter; cover plants; Cerrado